2020
DOI: 10.1002/mds.28379
|View full text |Cite
|
Sign up to set email alerts
|

Seven Solutions for Neuroprotection in Parkinson's Disease

Abstract: Parkinson's disease (PD) is a neurodegenerative disorder characterized by loss of dopaminergic neurons in the substantia nigra and accumulation of iron and alpha‐synuclein; it follows a characteristic pattern throughout the nervous system. Despite decades of successful preclinical neuroprotective studies, no drug has then shown efficacy in clinical trials. Considering this dilemma, we have reviewed and organized solutions of varying importance that can be exclusive or additive, and we outline approaches to hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 91 publications
(134 reference statements)
2
33
0
Order By: Relevance
“…However, the use of an enrichment strategy with more restrictive enrollment criteria, narrowing the study population on the basis of well-defined pharmacodynamic biomarkers of the studied therapeutic target, could offer an attractive starting point for success in disease modification in PD. Similar suggestions have been made recently by others ( Espay et al, 2020 ; Devos et al, 2021 ). The enormous investment in disease modification clinical trials over the past couple of decades should convince stakeholders that the strategy of “just keep doing the same” will likely only lead to further waste of time and resources, whereas the concept of a well-informed “less is more” rationale proposed here could not only be scientifically sound, but financially pertinent, as it may yield a new opportunity of turning failure to success.…”
Section: From Preclinical Success To Clinical Disappointment: Possibl...supporting
confidence: 91%
See 2 more Smart Citations
“…However, the use of an enrichment strategy with more restrictive enrollment criteria, narrowing the study population on the basis of well-defined pharmacodynamic biomarkers of the studied therapeutic target, could offer an attractive starting point for success in disease modification in PD. Similar suggestions have been made recently by others ( Espay et al, 2020 ; Devos et al, 2021 ). The enormous investment in disease modification clinical trials over the past couple of decades should convince stakeholders that the strategy of “just keep doing the same” will likely only lead to further waste of time and resources, whereas the concept of a well-informed “less is more” rationale proposed here could not only be scientifically sound, but financially pertinent, as it may yield a new opportunity of turning failure to success.…”
Section: From Preclinical Success To Clinical Disappointment: Possibl...supporting
confidence: 91%
“…The heterogeneity of sporadic PD remains an active field of research to accurately understand pathophysiology and the impact of independent and simultaneous pathologies, with the intention to inform prognosis, and shape therapeutic development for target-/group-, and individual specific disease-modifying therapies ( Mestre et al, 2021 ). Heterogeneity among individual patients is significant to the point that PD may be more appropriately called a syndrome with multiple causes ( Devos et al, 2021 ).…”
Section: From Preclinical Success To Clinical Disappointment: Possibl...mentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent review Devos and co-workers have reported that "Despite decades of successful preclinical neuroprotective studies, no drug has then shown efficacy in clinical trials." [99]. According to this and other publications, effective neuroprotective therapy is still an unmet need both in PD and MSA.…”
Section: Innovative Strategy For Pd and Msa Therapymentioning
confidence: 76%
“…Even though a causal therapy for these diseases does not currently exist, emerging evidence points out that life style modification can dramatically slow down the disease progression [ 3 , 4 ]. Moreover, new neuro-protective drugs are under study [ 5 ], which will be likely effective only if administered in very early, pre-clinical stages of the pathology [ 6 ]. This points out the need for early markers of neurodegeneration.…”
Section: Introductionmentioning
confidence: 99%